2017
DOI: 10.1016/j.jsxm.2017.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Health Competencies for Undergraduate Medical Education in North America

Abstract: Introduction The number of hours spent teaching sexual health content and skills in medical education continues to decrease despite the increase in sexual health issues faced by patients across the lifespan. In 2012 and 2014, experts across sexuality disciplines convened for the Summits on Medical School Education and Sexual Health to strategize and recommend approaches to improve sexual health education in medical education systems and practice settings. One of the summit recommendations was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 9 publications
1
22
0
1
Order By: Relevance
“…43 Bayer et al reported on the competency development process that experts across sexuality disciplines used to develop comprehensive, standardized sexual health competencies for undergraduate medical education to address the wide range of sexual concerns that patients experience. 44 This particular initiative built off the model process described by Eckstrand et al and resulted in the articulation of 20 sexual health competencies and 34 qualifiers aligned with the eight overall domains of competence as delineated in the PRCS. Bayer et al slightly modified the Eckstrand process to include psychological aspects of sexual health, as an integrated biopsychosocial approach is so critical to addressing sexual health issues.…”
Section: Education Competencies For Female Genital Cuttingmentioning
confidence: 99%
“…43 Bayer et al reported on the competency development process that experts across sexuality disciplines used to develop comprehensive, standardized sexual health competencies for undergraduate medical education to address the wide range of sexual concerns that patients experience. 44 This particular initiative built off the model process described by Eckstrand et al and resulted in the articulation of 20 sexual health competencies and 34 qualifiers aligned with the eight overall domains of competence as delineated in the PRCS. Bayer et al slightly modified the Eckstrand process to include psychological aspects of sexual health, as an integrated biopsychosocial approach is so critical to addressing sexual health issues.…”
Section: Education Competencies For Female Genital Cuttingmentioning
confidence: 99%
“…HCPs working with AYA males should feel comfortable with and be skilled in delivering SRH care to all AYA males, including sexual and gender minorities, or know where to make referrals to competent providers and/or those with specialized expertise. While competencies are established for general SRH education and care [21] and lesbian, gay, bisexual, transgender, and queer healthcare [22], SRH competencies for AYA males are lacking [23]. As a result, HCPs often do not receive adequate SRH education and patient care opportunities while in training [24].…”
Section: Hcp Competenciesmentioning
confidence: 99%
“…The expression of sexuality is an integral part of every person, it is a basic human right, and it continues throughout life, regardless of age or physical state. Despite the increase in sexuality issues faced by individuals across the lifespan, the number of hours spent teaching sexuality content and skills in medical education is limited (Bayer et al, 2017;Shindel et al, 2016). Health professionals are requesting more psychosocial and practical education on topics including fertility and sexuality to address these topics with clients proficiently (Bradford et al, 2018;Verrastro et al, 2020).…”
Section: Introductionmentioning
confidence: 99%